Trinitarian Missiology As An Effort to Establish Interfaith Dialogue and Relation in Indonesia - Yohanes Krismantyo Susanta (Conference Series, 2020)
This paper shows that the Christian mission is often understood only as an attempt to make a person become Christians. The paradigm was born as a result of the practice of Christian mission that laden with discrimination and injustice and tend to reject differences. That's necessary to grasp the understanding of Christian mission as the mission of the triune God, not the mission of the church. By using the library research method with an interdisciplinary approach, this paper offers the mission model of the Triune God (trinitarian missiology) as a humanitarian mission and the church is invited to participate in it to manifest God's mission to all creation. Christian mission also means seeking interfaith dialogue in fighting and overcoming social problems such as poverty, injustice, and others as being common to other faiths (the other). The Christian mission which rests on the doctrine of the trinity is not a barrier to dialogue but emphasises the importance of unity in diversity.